2019
DOI: 10.1128/msphere.00183-19
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Stabilization of a Panel of Picornaviruses

Abstract: Several viruses encounter various bacterial species within the host and in the environment. Despite these close encounters, the effects of bacteria on picornaviruses are not completely understood. Previous work determined that poliovirus (PV), an enteric virus, has enhanced virion stability when exposed to bacteria or bacterial surface polysaccharides such as lipopolysaccharide. Virion stabilization by bacteria may be important for interhost transmission, since a mutant PV with reduced bacterial binding had a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 33 publications
3
44
0
Order By: Relevance
“…Interactions with bacteria have previously been demonstrated to promote the stability of picornaviruses (15,16) and reoviruses (16,17). We hypothesized that bacterial stabilization of environmental IAV via direct interactions may be one mechanism that the virus exploits to retain infectivity following release into the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Interactions with bacteria have previously been demonstrated to promote the stability of picornaviruses (15,16) and reoviruses (16,17). We hypothesized that bacterial stabilization of environmental IAV via direct interactions may be one mechanism that the virus exploits to retain infectivity following release into the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Direct binding to gram-positive and gram-negative bacteria enhances the thermostability of poliovirus [10], Coxsackievirus B3 [5], HNoV [7,8], and reovirus [9], whereas the thermostability of Mengo and Aichi picornaviruses is strengthened by gram-positive and gram-negative bacteria, respectively [5]. Interestingly, both gram-positive and gram-negative bacteria also provide protection from bleach treatment to Aichi, Mengo, and poliovirus [5]. Moreover, binding of HNoV to HBGAs protects the virus from heat stress [8].…”
Section: Bacteria and Bacterial Components Influence Virion Stabilitymentioning
confidence: 99%
“…Human rotavirus and norovirus interact with polymorphic human histo-blood group antigens (HBGAs), and this interaction is thought to be important for infection (32). LPS stabilizes coxsackievirus B3 (CVB3) in vitro, but CVB3 is more sensitive to microbiota perturbation than poliovirus (11,12), indicating that it may have distinct glycan binding specificity. Bacterial LPS and peptidoglycan also increase reovirus thermostability (33), but the detailed glycan binding specificity is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We found that long N-acetylglucosamine (GlcNAc)containing polysaccharides can stabilize poliovirus but that a six-unit GlcNAc oligosaccharide, GlcNAc6, could not. Recent comparison studies of poliovirus with other members of the Picornaviridae, such as coxsackievirus B3, Aichi virus, and mengovirus, revealed shared and distinct effects of bacteria on virion stability (12).…”
mentioning
confidence: 99%